Mesoscale modelling of a masonry building subjected to earthquake loading - Chisari,C; Macorini,L; Izzuddin,B (Journal of Structural Engineering, 2020)
Masonry structures constitute an important part of the built environment and architectural heritage in seismic areas. A large number of these old structures showed inadequate performance and suffered substantial damage under past earthquakes. Realistic numerical models are required for accurate response predictions and for addressing the implementation of effective strengthening solutions. A comprehensive mesoscale modeling strategy explicitly allowing for masonry bond is presented in this paper. It is based on advanced nonlinear material models for interface elements simulating cracks in mortar joints and brick/block units under cyclic loading. Moreover, domain decomposition and mesh tying techniques are used to enhance computational efficiency in detailed nonlinear simulations. The potential of this approach is shown with reference to a case study of a full-scale unreinforced masonry building previously tested in laboratory under pseudodynamic loading. The results obtained confirm that the proposed modeling strategy for brick/block-masonry structures leads to accurate representations of the seismic response of three-dimensional (3D) building structures, both at the local and global levels. The numerical-experimental comparisons show that this detailed modeling approach enables remarkably accurate predictions of the actual dynamic characteristics, along with the main resisting mechanisms and crack patterns.